Does managerial personality matter? Evidence from firms in Viet Nam - Smriti Sharma; Finn Tarp (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
Using novel data from micro, small, and medium firms in Viet Nam, we estimate the relationship between behavioural and personality traits of owners/managers - risk attitudes, locus of control, and innovativeness - and firm-level decisions. We extend the analysis beyond standard metrics of firm performance such as revenue and growth to study intermediate investments, including product innovation, worker training, and adoption of workplace safety measures that are potentially conducive to observed firm performance. Our results show that innovativeness and locus of control are positively correlated with revenue while risk aversion predicts lower revenue. Risk aversion is positively correlated with the adoption of safety measures. Innovativeness, as expected, is associated with an increased probability of product innovations. An internal locus of control predicts higher probability of investments, innovations, and worker training. Heterogeneity analyses indicate that innovativeness and risk aversion matter more for firm outcomes in provinces characterized by better business climate. Our results are robust to a variety of checks. We contribute to a nascent and rapidly growing literature on the importance of managerial capital by shedding light on the role of managerial personality characteristics for decision-making in firms in a dynamic transition economy.
Keywords: D81; J24; L25; L26; 330; entrepreneurship; SMEs; firm performance; personality; risk attitudes; Viet Nam